Who needs strong leaders? - Alberto Chong; Mark Gradstein (Inter-American Development Bank, Research Department, 2008)
This paper's model suggests that a strong leader, sometimes with little legislative oversight, may nevertheless benefit from public support. The argument is that this support is induced as an attempt by the poor to counter the subversion of public protection of property rights by the rich, and to achieve this goal they are often willing to pay the price of the leader's diversion of tax revenues for private use. The paper then examines survey data on individual attitudes toward strong leadership and finds their pattern to be consistent with the model's predictions; specifically, support for strong leadership is inversely related to individual income and to countrywide income inequality.
Keywords: 330